Design of silane crosslinkable high density polyethylene compounds for automotive fuel tank application - Wan Abdul Rahman, Wan Aizan; Chen, Chan Hoong; Cheah, Eng Chai; Mazlan, Mohd. Nazrul Hisyam; Lee, Tin Sin; Ahmad Rupaii @ Aziz, Norhaliza (Universiti Teknologi Malaysia, 2005)
A formulation was designed to produce silane crosslinkable HDPE compound extrusion blow suitable for extrusion blow molding by melt blending technique on Magicmolding machine. The formulations consist of HDPE as the base polymer, a carrier chemical pack containing an organic unsaturated silane and a free radical generating agent and condensation catalyst. In designing and formulating silane crosslinkable blow molded HDPE compounds with satisfactory properties, ASTM D 2647 was used as the reference. Grafting and crosslinking reaction was proposed for the formulated system. The product was characterized for the chemical, thermal, physical and mechanical properties. The chemical reactions during grafting and crosslinking involved a three step mechanisms. Extrusion blow molded bottle were stored in water for curing at various temperature and time. DSC, FTIR and TGA were used to determine the chemical groups involved in the reactions and gel contents were determined in parallel. The results from curing showed that a further formation of Si-O-Si crosslink’s took place after the point at which maximum gel contents has been reached. Mechanical measurements indicated that further crosslink’s were formed within the existing gel. Suitable range concentration relating to 100 parts of base polymer was found for vinyltrimethoxysilane (VTMO) to be between 1.6 to 2.0 phr. The concentration of dicumyl peroxide (DCP) initiator was between 0.1to 0.5 phr. The concentration of dibutyltin dilaurate (DBTL condensation catalyst) was being 0.005 to 0.02. When the DBTL amount was less than 0.005 phr, the crosslinking reaction did not proceed sufficiently. As the DBTL amount was larger than 0.02 phr, local crosslinking proceeds in the extruder at the time of extrusion, results in great deterioration of the products. The selected components used in the formulation are HDPE grade HB6200, vinyltrimethoxysilane (VTMO) as the crosslinking agent, dicumyl peroxide (DCP) as the initiator, dibutyltin dilaurate (DBTL) as the condensation catalyst and Irganox 1010 as the antioxidant. The blow molded bottle properties and processability of the compound depends on the formulation and process parameter. Permeation rate of the fuel decreased proportionally with the addition of EVOH in PE structures. By taking the minimum rate of 1.14 gram petrol/day, it has clearly stated that the wall layer complies the EPA emissions regulations saying that a vehicle must emit no more than a total of 2.0 gram of hydrocarbon; measured during the diurnal ( 24 hours ) cycle. Also when using diesel as fuel, implementing EVOH content of 1% and 0.5mm off thickness, the permeation rate required by the standard of 0.35 gram/day is already achieved.